ATTITUDES OF EFL STUDENTS REGARDING LEARNER AUTONOMY IN ENGLISH VOCABULARY ACQUISITION - Suhardiana, I Putu Andre (Institut Hindu Dharma Negeri Denpasar, 2021)
Practical English communication for EFL students is wholly based on their vocabulary. However, learner autonomy (LA) is critical for EFL students’ vocabulary acquisition. The purpose of this research is to find out the viewpoints of students regarding LA when it comes to acquiring English vocabulary. There were 100 students from the college majoring in English Language Education Department completed the closed questionnaire, and 7 students participated in semistructured interviews. The research established that while participants intellectually recognized the relevance of LA in learning English vocabulary, they demonstrated a lack of interest in LA in learning English vocabulary on an emotional and behavioral level. These findings may help explain how to improve English teaching and learning, particularly English vocabulary teaching, in the context of other comparable EFL and research.